Discourses of antiracism in France - Lloyd, Catherine (Routledge revivals., 2018)
First published in 1998, this book is an examination of antiracist discourses and practices in France. It sets out to trace the development of post-war French antiracism through the life of antiracist organizations, setting this within a broader historical, political and social context. It breaks new ground in that it analyses antiracism as a body of ideas in its own right, rather than as a mirror image of racism. The author uses previously unpublished archival material from French organizations combined with observations from current events. She argues that antiracist discourses and practices are structured around four main themes: discrimination, representation, solidarity and hegemony. While perceptions of discrimination have evolved into complex understandings of social exclusion, the representational functions of antiracist groups were challenged by immigrant workers movements themselves. Solidarity remained central to antiracist practices in different political contexts. Underpinning these features lies a hegemonic social project through which antiracists have sought to promote a 'common sense' through political and educational campaigns. The author concludes that French antiracism although constantly changing and refocusing is now a pluralist, transversal, hegemonic movement and an important component of civil society.